Detection Principles of Temperature Compensated Oscillators with Reactance Influence on Piezoelectric Resonator - Vojko Matko; Miro Milanovič (Sensors, 2020)
This review presents various ways of detection of different physical quantities based on the frequency change of oscillators using piezoelectric crystals. These are influenced by the reactance changes modifying their electrical characteristics. Reactance in series, in parallel, or a combination of reactances can impact the electrical crystal substitute model by influencing its resonant oscillation frequency. In this way, various physical quantities near resonance can be detected with great sensitivity through a small change of capacitance or inductance. A piezoelectric crystal impedance circle and the mode of frequency changing around the resonant frequency change are shown. This review also presents the influence of reactance on the piezoelectric crystal, the way in which the capacitance lost among the crystal’s electrodes is compensated, and how the mode of oscillators’ output frequency is converted to lower frequency range (1–100 kHz). Finally, the review also explains the temperature–frequency compensation of the crystals’ characteristics in oscillators that use temperature–frequency pair of crystals and the procedure of the compensation of crystals own temperature characteristics based on the method switching between the active and reference reactance. For the latter, the experimental results of the oscillator’s output frequency stability (fout = ±0.002 ppm) at dynamical change of environment temperature (0–50 °C) are shown.